2010
DOI: 10.1080/14680629.2010.9690337
|View full text |Cite
|
Sign up to set email alerts
|

General Rheological Properties of Fractionated Switchgrass Bio-Oil as a Pavement Material

Abstract: An alternative approach for decreasing the demand and dependency for crude petroleum/bitumen binders is the use of bio-binders in three different ways: a direct alternative binder (100% replacement), a bitumen extender (25% to 75% replacement), or a bitumen modifier (<10% replacement). In this paper, the applicability of developing biobinders from switchgrass bio-oil fractions to be utilized as a direct alternative has been investigated. The results showed that the relationship between viscosity and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 9 publications
0
39
0
1
Order By: Relevance
“…Fini et al [30] and Mills-Beale et al [3] found that bio-oils generated from swine waste can enhance the low temperature performance of asphalt binders and save the cost. Raouf and Williams [4] studied the rheology of bio-oils from cornstover and found that the rheological properties of cornstover bio-oils are similar and comparable to bitumen binders and can be a renewable alternative for traditional asphalt binders. Raouf et al [24] proceeded further to add polymers into the bio-oil and investigated the properties of bio-oils modified by polymers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fini et al [30] and Mills-Beale et al [3] found that bio-oils generated from swine waste can enhance the low temperature performance of asphalt binders and save the cost. Raouf and Williams [4] studied the rheology of bio-oils from cornstover and found that the rheological properties of cornstover bio-oils are similar and comparable to bitumen binders and can be a renewable alternative for traditional asphalt binders. Raouf et al [24] proceeded further to add polymers into the bio-oil and investigated the properties of bio-oils modified by polymers.…”
Section: Introductionmentioning
confidence: 98%
“…Using alternative materials is one of the most effective and environmentally friendly ways to solve this problem. Recently researcher have found that bio-oils can be generated from such biomass materials as microalgae [1], animal waste [2,3], cornstover [4], urban yard waste [5], tea and coffee residue [6,7], rapeseed and soybean [8,9], etc. Some of these bio-oils have been used to modify or partially replace the petroleum asphalt binders in the asphalt pavement structure [2][3][4]10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Bio-oil behavior at intermediate and high temperatures is similar to that of a conventional bitumen [8], but it is too stiff, and is quite brittle at low temperatures. However, that problem could be solved by adding ground rubber from used tires (GTR) in order to obtain a bio-binder with a very good performance [9].…”
Section: Introductionmentioning
confidence: 71%
“…The reduced low temperature performance is offset by the ability to introduce a higher reclaimed asphalt pavement content into asphalt containing bio‐oil . Bio‐oils derived from corn stover, waste wood, switchgrass, and oak have all been identified as having performance properties that are similar to and comparable with petroleum‐based asphalt binders.…”
Section: Opportunities For Bio‐based Productsmentioning
confidence: 99%